Urban aquaculture - Costa-Pierce, Barry A. (CABI, 2005)
Millions of people are moving from rural areas to coastal cities. Meeting the basic human needs for protein foods in the future will be a difficult challenge. Fishery products are the world's most important source of animal protein, which has led to a doubling of the demand for fish since the 1950s